IMPLEMENTATION OF THE CONCEPT OF BRAND EQUITY AND CONSUMER SATISFACTION IN THE BERYL'S CHOCOLATE MALAYSIA BRAND (Case Study on Students Participating in KKL Management and Accounting Study Program Of STIE Sutaatmadja Subang 2019) - Mira Milatusadia; Rakhee Istiqomah Begum Irlambang; Bismantara Bismantara (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2020)
This research aims to describe about the implementations concepts of brand equity and consumers satisfaction on Beryl’s chocolate which is the famous chocolate brand in Malaysia. Beryl’s is brand with best rating in Malaysia (noumantour.com). The methods of data collections on this research are observation, literature study and questionnaire. Populations on this research are STIE Sutaatmadja Subang students who are the participants of KKL 2019 entirety, both of accountancy and management majors there are 139 college students. The writers utilize slovin method (? = 5%) in order to determine number of samples there are 104. Based on this research, the implementation of brand equity concepts on Beryl’s Chocolate is quite good. While the questionnaire on consumer satisfaction is quite high, averagely in the amount of 91,25% respondent clarify that satisfied by Beryl’s chocolate.